Child tracking and hidden activities observation system through mobile app - Mohammad Jahangir Alam; Tanjia Chowdhury; Sohrab Hossain; Shusmoy Chowdhury; Tanmoy Das (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
The world is changing rapidly due to information technology, and all the people around the world are busy with their jobs, and business, adjusting to this race. Now, parents are giving more time at their business, office, and jobs, instead of passing the time at home, but they always get worried and scared about their children due to abuse of Information Technology and the country's law and order situation. So, parents are wanted to track and monitor their child's activities and location from anywhere to resolve their pressure. But is not possible for every parent to monitor their child physically due to many reasons. This paper presents a system that will help parents monitor their child activities from anywhere using a mobile phone to solve the problem. This android app uses global positioning system (GPS) and mobile services to find the child location and secretly stored all the call logs, hort message service (SMS) logs, contact lists, and accurate locations without knowing the children. Children assume that they are using Facebook, browsing the net or watching videos from youtube. It will not hamper any activities of the child. Parents can check all the activities of children using this app.